Comparative Study of Conservative and Surgical Management of Clavicle Fractures in Iraqi Adults: A Prospective Cohort Study at a Al-Hilla General Teaching Hospital - Al-Janabi , Kaisser Kareem Jassim; Fanharawy, Montadher Najem Oubaid; Alkadhim, Ali Dheyaa Abed (American Journal of Biomedicine and Pharmacy, 2026)
Background: Clavicle fractures represent one of the most frequently encountered skeletal injuries in orthopaedic practice, accounting for approximately 2.6–5% of all fractures in adults. Despite their high prevalence, the optimal management strategy—conservative or surgical—remains a subject of ongoing clinical debate, particularly within the Iraqi healthcare context where epidemiological and functional outcome data are sparse. Objectives: To compare functional outcomes, radiological union rates, complication profiles, and patient satisfaction between conservative and surgical management of displaced clavicle fractures in Iraqi adults treated at a Al-Hilla General Teaching Hospital. Methods: A prospective cohort study was conducted between January 2021 and December 2023. A total of 130 adult patients with acute displaced midshaft or lateral third clavicle fractures were enrolled and allocated to either conservative management (sling immobilisation, n=68) or surgical intervention (open reduction and internal fixation using plate and screws, n=62) based on standardised clinical criteria. Primary outcomes included the Disabilities of the Arm, Shoulder and Hand (DASH) score and Visual Analogue Scale (VAS) for pain at serial follow-up intervals (6 weeks, 3, 6, and 12 months). Secondary outcomes included time to radiological union, return to work, complication rates, and patient-reported satisfaction. Results: The surgical group demonstrated significantly superior DASH scores at all follow-up intervals compared to the conservative group (p<0.001). Mean time to radiological union was 11.4 ± 2.6 weeks in the surgical cohort versus 14.8 ± 3.2 weeks in the conservative cohort (p<0.001). Non-union occurred in 11.8% of conservatively managed patients compared to 3.2% in the surgical group (p=0.048). Return to occupational activity was significantly earlier in the surgical group (7.6 ± 2.9 weeks vs. 11.3 ± 3.8 weeks; p<0.001). While the surgical group exhibited specific complications including wound infection (6.5%) and implant-related issues (8.1%), the overall complication burden was significantly lower compared to the conservative group (32.3% vs. 66.2%; p<0.001). Conclusion: Surgical management of displaced clavicle fractures in Iraqi adults yields significantly better functional recovery, earlier return to work, and lower overall complication rates compared to conservative management. These findings support the selective use of operative fixation—particularly open reduction and internal fixation with plate and screws—as the preferred approach for significantly displaced midshaft and lateral third clavicle fractures in the Iraqi adult population, subject to appropriate patient selection.